انماط الاستغلال الزراعي في محافظة اريحا 1970-2008 - أ. لؤي ابو ريدة (My University, 2010)
Jericho Governorate lies below sea level and this gives it a comparative advantage in terms of high temperatures in summer and winter compared with other geographical areas, where the Valley's 'natural greenhouse' in winter ripens most crops, and that the climate is convenient for some agricultural crops such as palm And bananas, which require high temperatures. These characteristics make Jericho area maintain the agricultural harvest in winter when the produce of vegetables and fruits in other areas of Palestine decreases. This region begins production of vegetables early in October until the end of May to become the main source of crops for other relatively colder places in the region.
The study aimed to shed light on the conditions related to the agricultural sector which forms the backbone of the economy of the region that suffers from many problems, notably, the lack of water, soil problems and the problems of production and marketing. The study also aimed to identify the fine conditions and human factors affecting the growth of agriculture and arable land uses and to identify economic and social characteristics of farms in the region. The study also surveyed stages of development and the uses of arable land in the Governorate and the effect of Israeli practices against the agricultural sector.
The descriptive analytical approach was used, data collected from institutions and relevant bodies, apparatuses, and references in addition to field work. A questionnaire distributed to farmers was also used. Then, data was processed and analyzed using spss analysis program.
The study reached the following findings:
1. Natural factors and the climate play a major role in the selection of crop growth.
2. Vegetables are the top agricultural crops in the Governorate, and form (44%)of its economy.
3. The Study found that the region has been suffering from a severe shortage of water.
4. The findings revealed the effect of Israeli settlements on the agricultural system through control of water, (40%), land confiscation and transportation hindering for security reasons.
The study presented the following recommendations to develop the agricultural sector:
- Solving the marketing problem by establishing new markets, and
- Providing more water supplies through solving the water crisis in the region.

تتميز محافظة أريحا بكونها تقع تحت مستوى سطح البحر وهذا يعطيها ميزة نسبية من حيث ارتفاع درجات الحرارة صيفاً وشتاءً عن باقي المناطق الجغرافية، حيث تعتبر منطقة الأغوار دفيئة طبيعية في فصل الشتاء, يبكر فيها الإنتاج لمعظم المحاصيل الزراعية، وكذلك تعتبر مناخاً جيدا لبعض المحاصيل الزراعية مثل النخيل والموز والتي تحتاج الى درجات حرارة عالية مما جعل المحافظة منطقة حيوية وزراعية ذات محصول شتوي يأخذ بالإنتاج عندما يفتقد إنتاج الخضراوات والفواكه في المناطق الأخرى من فلسطين وتبدأ هذه المنطقة بالإنتاج الزراعي للخضراوات من بداية شهر تشرين الأول حتى نهاية أيار وتشكل بذلك المحصول الرئيس للمناطق الباردة .
لقد استهدفت هذه الدراسة إلقاء الضوء على أوضاع المحافظة من النواحي الأساسية المرتبطة بالقطاع الزراعي الزراعة، الذي يشكل العمود الفقري لاقتصاد المنطقة والذي يعاني من مشكلات عديدة أهمها قلة المياه ومشاكل التربة ومشاكل الإنتاج والتسويق ، كما هدفت الدراسة إلى التعرف إلى الظروف والعوامل البشرية المؤثرة على النمو الزراعي واستخدامات الأراضي الزراعية بالإضافة إلى التعرف على الخصائص الاقتصادية والاجتماعية للمزارع في تلك المناطق, كما قامت الدراسة بتتبع مراحل التطور الزراعي واستعمالات الأرض في المحافظة خلال العقود الماضية وما تخللها من ممارسات إسرائيلية استهدفت القطاع الزراعي .
فقد اعتمدت الدراسة على المنهج الوصفي التحليلي حيث تم جمع البيانات والمعلومات من المؤسسات والنشاطات والمراجع والمصادر ذات العلاقة بالإضافة إلى العمل الميداني الذي تمثل بالاستبيان الذي تم توزيعه على المزارعين ليتم بعد ذلك معالجة البيانات وتحليلها بواسطة برنامج spss.
وتوصلت الدراسة إلى جملة من النتائج أهمها.
1. ان العوامل الطبيعية وأهمها المناخ تلعب دورا كبيرا في النظام الزراعي.
2. تحتل الخضروات الدرجة الأولى في الزراعة داخل المحافظة والتي بلغت نسبتها (44%).
3. ان المحافظة تعاني من نقص شديد بالمياه .
4. ان هنالك تأثير للمستوطنات الإسرائيلية على النظام الزراعي من خلال السيطرة على المياه والذي بلغ نسبتهم (40%) ومصدرة الأراضي وإعاقة تنقل بعض المزارعين بحجج أمنية.
كما حظيت الدراسة ببعض التوصيات التي يمكن من خلالها تطوير وتنمية القطاع الزراعي والتي يمكن حصرها بحل مشكلة التسويق من خلال فتح أسواق جديدة إمام المزارع والعمل على توفير المياه الزراعية وذلك بإيجاد اتفاقيات مع الجانب الإسرائيلي .
انماط الاستغلال الزراعي في محافظة اريحا 1970-2008